2019
DOI: 10.21203/rs.2.15389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research on the health of and interventions for family caregivers of people with dementia: a bibliometric analysis of research output during 1988–2018

Abstract: Background: Dementia is a large and growing health problem, and since the majority of dementia patients live at home, caring responsibilities generally fall to family members. Caregivers are often inadequately supported by formal health services and have poorer psychological and physical health. Our study aimed to compare the contributions of publications from different countries, institutions and authors and present a bibliometric analysis to determine the future hotspots and trends in research on the health … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…This was not unusual because the U.S. is the most active country in the study of geriatric nursing, and U.S. researchers rank first when it comes to scientific production in medicine, health, and nursing [30,32,33]. Additionally, it was revealed that the large scientific community, big research budget, higher national self-citation, desire to publish in national journals, and developed country are also contributing factors in the USA being a pioneer in this field [34,35]. In the USA, the population age sixty-five years and over is estimated to nearly double over the next three decades, from 48 million to 88 million by 2050, and the need for more research in this field is felt.…”
Section: Discussionmentioning
confidence: 99%
“…This was not unusual because the U.S. is the most active country in the study of geriatric nursing, and U.S. researchers rank first when it comes to scientific production in medicine, health, and nursing [30,32,33]. Additionally, it was revealed that the large scientific community, big research budget, higher national self-citation, desire to publish in national journals, and developed country are also contributing factors in the USA being a pioneer in this field [34,35]. In the USA, the population age sixty-five years and over is estimated to nearly double over the next three decades, from 48 million to 88 million by 2050, and the need for more research in this field is felt.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Shi et al [ 25 ] studied research on family caregivers of people with dementia, highlighting that the increased prevalence of dementia in very old people and their lengthening life expectancy can increase the risk of diverse health problems in family members, including depression, stress, anxiety, and other physical or psychological disorders. Caregivers have even been called “silent patients” or “secondary patients” whose needs should be addressed through specific strategies to protect and provide them with the required support; such strategies show unequal development across different countries [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are indeed other database for bibliometric analysis, such as Pubmed and Scopus. However, to the best of our knowledge, Thomson Reuters' WOS is the most appropriate database for performing bibliometric analysis [37]. Second, some important studies related to research area of psycho-oncology in non-English language were not included and analyzed.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Second, some important studies related to research area of psycho-oncology in non-English language were not included and analyzed. Third, there were differences between the bibliometric analysis results and the real research situations, since some latest published high-quality studies were not focused on because of their low citation frequency [37]. Therefore, it may be necessary to update the bibliometric analysis in the future.…”
Section: Study Limitationsmentioning
confidence: 99%